Electronically Tunable Current-mode High-order Ladder Low-pass Filters Based on CMOS Technology - Kunto, Terdsak; Prommee, Pipat; Abuelma'atti, Muhammad Taher (Společnost pro radioelektronické inženýrství, 2015)
This paper describes the design of current mode low-pass ladder filters based on CMOS technology. The filters are derived from passive RLC ladder filter prototypes using new CMOS lossy and lossless integrators. The all-pole and Elliptic approximations are used in the proposed low-pass filter realizations. The proposed two types of filter can be electronically tuned between 10kHz and 100MHz through bias current from 0.03µA to 300µA. The proposed filters use 1.5 V power supply with 3 mW power consumption at 300 µA bias current. The proposed filters are resistorless, use grounded capacitors and are suitable for further integration. The total harmonic distortion (THD) of the low-pass filters is less than 1% over the operating frequency range. PSPICE simulation results, obtained by using TSMC 0.18µm technology, confirm the presented theory.
Keywords: CMOS; current mode; ladder filters; all-pole; elliptic; low-pass filter